A longitudinal study of primary school EFL learning motivation in CLIL and non-CLIL settings. (November 2019) - Pladevall-Ballester, Elisabet
Content and language integrated learning (CLIL) is often introduced in school settings in an attempt to increase exposure to the foreign language (FL) and promote motivation and positive language attitudes. The present study examines how language learning motivation develops over the course of two academic years in two types of instruction setting (CLIL and non-CLIL) with equal but low exposure to the FL and in two types of CLIL subject (science and arts and crafts). Data were collected from four primary schools in fifth and sixth grades by means of a motivation questionnaire. Differences between groups are observable in relation to the second language (L2) learning experience dimension of motivation in favour of the CLIL learners, who increased their motivation over time. Type of CLIL subject was found to be relevant also only in relation to the L2 learning experience dimension of motivation. Even in low exposure contexts, FL motivation is promoted and maintained over time by adding CLIL to the language experience of young learners.